Effect of Dilute Acid Pretreatment of Vegetable Waste on Sugar Production and Inhibitor Formation - Denistira Fazlur Rahman; Hakun Wirawasista Aparamarta; Arief Widjaja (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
Vegetable waste is an organic waste with high cellulose and hemicellulose and low lignin content. The cellulose and hemicellulose chains can be broken down by pretreatment using sulfuric acid to obtain reducing sugar. To avoid the formation of degradation products that have the potential as inhibitor compounds, the temperature of the pretreatment operation was carried out at 121 and 125 for 60 minutes with sulfuric acid concentrations varying from 0.5% to 1.5% (v/v). The solid and liquid ratio (S/L) was 5% (w/v). From the experiments, the highest total reducing sugars of 7.068 g/L was obtained by pretreatment conditions at 121 for 60 minutes with a sulfuric acid concentration of 1% (v/v). Meanwhile, the lowest total reducing sugar of 2.764 g/L was produced during the pretreatment operating conditions at 125 for 60 minutes with a sulfuric acid concentration of 1% (v/v). Under the present experimental condition, it was found that only a low level of degradation product was formed, which ensures excellent performance of bacterial growth in the subsequent fermentation process.